DO DEMENTIA CAREGIVERS HAVE WORSE HEALTH OUTCOMES AS COMPARED TO NON-CAREGIVERS IN A NATIONAL SAMPLE?. (16th November 2018) - Larsen, C; Richard, C; West, D
Abstract: Dementia caregivers often report poorer health as compared to non-caregivers and may engage in more unhealthy lifestyle behaviors. However, these results have been from small samples limited to single locations. Therefore, the purpose of this study was to compare dementia caregivers and non-caregivers along important health dimensions using data from the caregiving module and core module of the population-based, ethnically- and geographically-diverse Behavioral Risk Factor Surveillance System (BRFSS) survey. BRFSS data from 2015, 2016 and 2017 were merged, reweighted and reduced to include individuals who completed the optional caregiving module. All non-dementia caregivers were excluded. Logistic regression was used to analyze differences between caregivers and non-caregivers. Both caregivers (n=4, 210) and non-caregivers (n=164, 742) were overweight (M BMI: 28.7 and 28.0, respectively). After controlling for sex, age, education and race/ethnicity, the odds of being obese (BMI >30) were 1.181 times (95% CI: 1.04–1.337) higher among caregivers. Caregivers also had significantly higher odds of being diagnosed with depressive disorder (OR=1.472; 95% CI: 1.290–1.669), having some form of arthritis (OR=1.378; 95% CI: 1.235–1.557), and having had a cardiovascular event (OR=1.286; 95% CI: 1.03–1.583). There were no significant differences in smoking status, physical activity participation, or binge drinking between caregivers and non-caregivers. Even after controlling for significant differences in demographic variables between the two groups, dementia caregivers appear to have worse health outcomes as compared to non-caregivers. However, self-reported behaviors did not significantly differ. Considering the expected growth in the number of caregivers, a deeper examination is needed into why these key health discrepancies exist.